2001
DOI: 10.4269/ajtmh.2001.64.207
|View full text |Cite
|
Sign up to set email alerts
|

Blood-brain barrier function in cerebral malaria in Malawian children.

Abstract: Abstract. Cerebral malaria (CM) is a serious complication of Plasmodium falciparum infection. Binding of parasitized erythrocytes to cerebral endothelium plays a key role in disease pathogenesis. Central nervous system signs and symptoms (coma, seizures, raised intracranial pressure) predominate in African children, whereas in adults, multiorgan system failure is more common. In this study we investigated whether changes in blood-brain barrier (BBB) structure and function are compatible with the signs and symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
111
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(117 citation statements)
references
References 19 publications
5
111
1
Order By: Relevance
“…The CSF albumin and IgG and IgM were not raised in Zairean children with CM compared with Swiss controls. However, in a more recent study from Malawi, the partition of albumin between circulating plasma and CSF showed subtle but measurable changes suggesting impairment of the BBB (Brown et al 2001). These findings have been confirmed in Kenyan children with CM (Mturi et al 2003) but the Kenyan study also found that the BBB was mildly impaired in children with malaria and seizures or those with a less severe degree of unconsciousness, suggesting that impairment of the BBB is not unique for CM.…”
Section: Studies Of the Functional Integritysupporting
confidence: 52%
See 1 more Smart Citation
“…The CSF albumin and IgG and IgM were not raised in Zairean children with CM compared with Swiss controls. However, in a more recent study from Malawi, the partition of albumin between circulating plasma and CSF showed subtle but measurable changes suggesting impairment of the BBB (Brown et al 2001). These findings have been confirmed in Kenyan children with CM (Mturi et al 2003) but the Kenyan study also found that the BBB was mildly impaired in children with malaria and seizures or those with a less severe degree of unconsciousness, suggesting that impairment of the BBB is not unique for CM.…”
Section: Studies Of the Functional Integritysupporting
confidence: 52%
“…This study found gaps between the ECs (Figure 3), with PRBC and non-PRBC in the brain parenchyma, but this only occurred in haemorrhages and there was no difference between those with CM and non-CM cases. Immunochemistry has shown distribution of the cell junction proteins occludin, vinculin and ZO-1 were altered in Vietnamese adults (Brown et al 1999) and Malawian children with CM (Brown et al 1999(Brown et al , 2001). In the perivascular space, there was a widespread macrophage activation suggesting that these cells had been exposed to plasma proteins.…”
Section: Morphological Studies Of the Blood-brain Barriermentioning
confidence: 99%
“…TGF-β mRNA and protein were expressed in CM post-mortem brain tissue from Malawian children infected with P. falciparum malaria [46] . TGF-β was also elevated in the CSF of Vietnamese patients with CM [47] . Furthermore, Thai patients with malaria had low levels of serum TGF-β, which were noted to increase after treatment with artesunate and mefloquine [48] .…”
Section: Decreased Activation Of Nf-κb In Blood Mononuclear Cells Of mentioning
confidence: 91%
“…In autopsy-derived samples from children with CM, there are conflicting results with one group showing loss of tight junction proteins and a lack of transendothelial leakage of fibrinogen, whereas a more recent report shows significant leakage of fibrinogen into the brain parenchyma [26,27]. Assessment of the integrity of the BBB can be determined in vivo with the use of retinal fluorescein angiography.…”
Section: Pathogenesismentioning
confidence: 99%